STUDENTS' PERCEPTIONS OF WATCHING ENGLISH MOVIE HABITS IN DEVELOPING ENGLISH SPEAKING SKILL AT THE ENGLISH STUDY PROGRAM OF FATMAWATI SUKARNO STATE ISLAMIC BENGKULU UNIVERSITY - Linda Sari, Maiya; Rizal, Syamsul; Haryanto, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT English speaking skill development is often hampered by limited exposure to authentic language and low student self-confidence. Although movie is recognized as an effective learning medium, research on students' perceptions of movie-watching as a natural learning process is still limited. This study aims to explore the perceptions, experiences, and aspects of speaking skills developed through the habit of watching English movies. This study used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews and documentation of 16 fourth-semester students of the English Language Education Study Program at UIN Fatmawati Sukarno Bengkulu who have good speaking skills. The study participants were selected using a purposive sampling technique, namely students who have good English speaking skills based on academic grades and oral communication skills. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The results showed that 100% of participants had a positive perception, viewing this habit not merely as entertainment, but as a deliberate self-directed learning strategy. This habit significantly improved micro-skills, especially vocabulary enrichment and pronunciation, through exposure to comprehensible input and shadowing techniques. In contrast, the development of macro-skills such as fluency and self-confidence is conditional. Improvement in these aspects is highly dependent on students' willingness to transform passive input into driven output through active practices, such as self-talk or creating vlogs. It was concluded that English movies are an effective pedagogical catalyst, but successful holistic development of speaking skills still requires active learning strategies and learner autonomy.